TERRY COOK, ed., Controlling the Past: Documenting Society and Institutions: Essays in Honor of Helen Willa Samuels - Dodge, Bernadine (Archivaria, 2012)
Controlling the Past: Documenting Society and Institutions: Essays in Honor of Helen Willa Samuels. TERRY COOK, ed. Chicago: Society of American Archivists, 2011. 434 p. ISBN 978-1-931666-36-9